IMPACT OF PERCEIVED BEHAVIORAL CONTROL, NEED FOR ACHIEVEMENT AND LOCUS OF CONTROL ON ENTREPRENEURIAL INTENTION - Jullimursyida (RADJA PUBLIKA, 2021)
This study aims to explore the effect of Perceived Behavioral Control, Need for Achievement and Locus of Control on Entrepreneurial Intention. Quantitative methods was applied and the data collection done by survey. The population of this study were university students in Aceh and North Sumatera. A total of 114 students were randomly selected and served as the respondents of this study. The technique of determining the sample using non probability sampling. The data analysis in this study used multiple regression. The result showed that the need for achievement had significant effect on entrepreneurial intention, Perceived Behavioral Control had a significant effect on Entrepreneurship Intention but Locus of Control was not had a significant effect on entrepreneurial intention.